Ambiguity and interaction in city design. The impact of superblock on architecture - Marco Russo (Techne, 2025)
The paper presents a series of reflections on the street as a place for relations, a significant aspect of European city design. This ‘new’ approach focuses more on interaction and the active use of outdoor spaces, starting from criticism of some solutions proposed by the Modern Movement by Team 10 members. However, this design vision has recently gained significant traction, marking a notable shift in European city redevelopment. The text explores the concepts behind public spaces where the interaction between inside and outside is becoming less distinct.